Healthcare professionals’ perspectives on the provision of sexual and reproductive health to young people in Malaysia - Abdul Hamid, Siti Hazariah; Fallon, Debbie (IIUM Press, 2020)
Objective: In Malaysia, sexual health issues among young people encompassing premarital sex, the incidence of STI including HIV/AIDS, unintended pregnancy, unsafe abortion and the practice of baby abandonment. Little is known about the provision of sexual health care for young people since it has not been examined in-depth in a Malaysian context. This study aimed to explore the perspectives of healthcare professionals who deliver sexual health services provision to young people within primary healthcare settings which included schools as part of an outreach programme. Methods: This qualitative study used a self-developed topic guide for in-depth interview with twenty-four healthcare professionals of several government health clinics in Malaysia. The aim was to understand healthcare professionals’ experiences of dealing with young people and their views on current sexual health services provision. The interview data were entered into Nvivo and analysed using thematic analysis. Results: The findings show that healthcare professionals regarded the use of the Adolescent Health Screening Form as a cornerstone for all initial interactions between and young people in health clinics. The findings also highlight the problem with an appointment system that includes lack of consultation times, privacy issues and the requirement of parental consent when dealing with unmarried young people. Conclusion: This study had recognized several facility-based obstacles that restricted sexual health services to young people in Malaysia. Their access to and the utilization of sexual health services are dependent on health care system improvement.